Dog Man - Book 1 - Pilkey, Dav 1966-; Beard, George (Fictitious character); Hutchins, Harold (Fictitious character); Garibaldi, Jose (New York, NY : Graphix, an imprint of Scholastic, 2016)
George and Harold create a new comic book hero in Dog Man, a crimefighter with the head of a police dog and the body of a policeman, who faces off against his archnemesis Petey the cat.
Keywords: Police -- Comic books, strips, etc; Dogs -- Comic books, strips, etc; Police -- Fiction; Dogs -- Fiction; Cartoons and comics; Action and adventure comics; Comic (Graphic works)